Antenatal Yoga and Murottal Al-Quran Therapy Decreasing Anxiety and Blood Pressure of Preeclampsia Risk Women - Mamlukah Mamlukah; Isti Kumalasari; Rizky Setiadi (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Pregnant women experience significant changes in physiological andpsychological functions. The process of adjusting to this new condition oftencauses anxiety. One of the pregnancy complications that is affected by anxiety ispreeclampsia. The purpose of this study was to identify the effects of antenatalyoga and murottal Al-Quran therapy on pregnant women at risk of preeclampsia.This study was conducted in primary health care in Majalengka, Indonesia, usingtrue experiment (pretest-posttest control group) design as many 40 respondentsdivided into 4 groups, Antenatal Yoga (AY), the Murottal Al-Qur’an Therapy(MAT), combination of yoga and murottal al-Quran, and control group.Respondents were taken by cluster and simple random sampling. The anxiety,blood pressure, sFlt-1, and PIGF levels of all respondents were measured after 12interventions. Data were analyzed with Kruskall-Wallis and One-way Anova tests.The antenatal yoga, murottal Al-Qur'an therapy, and its combination significantlydecrease anxiety (p=0.007), systole (p=0.006), and diastole (p=0.001) in pregnantwomen with the risk of preeclampsia. There were no significant differences ofsFlt-1 (p=0.286), PIGF (p=680) and ratio of sFlt-1/PIGF (p=969) among groups.The antenatal yoga, Murottal Al-Qur'an therapy, and it's combination effectdecreasing anxiety and blood pressure in pregnant women with the risk ofpreeclampsia in Majalengka.